An Exit-Price Income Statement. - Friedman, Laurence A. (The Accounting Review, 1978)
ABSTRACT: The exit-price approach to financial statement valuation has been criticized for the lack of a meaningful income statement. In this article, an income statement is designed that provides information about the resource flows which result in income generation. The proposed statement is divided into an operating section and a holding section. The traditional revenue recognition assumption is maintained in the operating section. Expenses are then matched with revenues based on a concept called "instantaneous matching." In the holding section of the statement, gains and losses are based on market price changes of assets held. The income statement uses both replacement costs and exit prices and yet reconciles with exit-price balance sheets. The result is that the strengths of a replacement cost income statement are combined with an exit-price oriented balance sheet.